Impairment of sugar transport in the vascular system acts on nitrogen remobilization and nitrogen use efficiency in Arabidopsis. Issue 6 (7th December 2022) - Hoffmann, Beate; Aubry, Emilie; Marmagne, Anne; Dinant, Sylvie; Chardon, Fabien; Le Hir, Rozenn
Abstract: Carbon (C) and nitrogen (N) metabolisms have long been known to be coupled, and this is required for adjusting nitrogen use efficiency (NUE). Despite this intricate relationship, it is still unclear how deregulation of sugar transport impacts N allocation. Here, we investigated in Arabidopsis the consequences of the simultaneous downregulation of the genes coding for the sugar transporters SWEET11, SWEET12, SWEET16, and SWEET17 on various anatomical and physiological traits ranging from the stem's vascular system development to plant biomass production, seed yield, and N remobilization and use efficiency. Our results show that intracellular sugar exchanges mediated by SWEET16 and SWEET17 proteins specifically impact vascular development but do not play a significant role in the distribution of N. Most importantly, we showed that the double mutant swt11 swt12, which has an impacted vascular development, displays an improved NUE and nitrogen remobilization to the seeds. In addition, a significant negative correlation between sugar and amino acids contents and the inflorescence stem radial growth exists, highlighting the complex interaction between the maintenance of C/N homeostasis and the inflorescence stem development. Our results thus deepen the link between sugar transport, C/N allocation, and vascular system development.